2014
DOI: 10.1111/pbr.12228
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis and quantitative trait locus mapping of PEG‐induced osmotic stress tolerance in cotton

Abstract: Water stress is one of the major abiotic stresses that adversely affect cotton production. Seedlings of 142 backcross inbred lines (BILs) derived from Pima cotton 'Pima S-7' (Gossypium barbadense L.) 9 Upland cotton 'Sure-Grow 747'(G. hirsutum L.) were evaluated in two tests for plant height, fresh shoot weight and root weight under two treatments (5% PEG and water-control conditions) using a hydroponic system in the greenhouse. The experiment in each test was a randomized complete block design with three repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…For the drought tolerance study, 10% of polyethylene glycol 8000 (PEG) was used to induce osmotic stress in one hydroponic system as the treatment test following Abdelraheem, Hughs, et al. (2015) and Abdelraheem, Mahdy, and Zhang (2015). For the control test, the RILs and the two parents in the other hydroponic system were irrigated with tap water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the drought tolerance study, 10% of polyethylene glycol 8000 (PEG) was used to induce osmotic stress in one hydroponic system as the treatment test following Abdelraheem, Hughs, et al. (2015) and Abdelraheem, Mahdy, and Zhang (2015). For the control test, the RILs and the two parents in the other hydroponic system were irrigated with tap water.…”
Section: Methodsmentioning
confidence: 99%
“…Pima cotton is expected to be a promising species for abiotic stress (such as drought and salt) tolerance due to it originating from sea coast (Tiwari et al, 2013a(Tiwari et al, , 2013b, but there is a lack of genetic information on abiotic stress tolerance in pima cotton (Flowers, 2004). Drought and salt stresses have a negative impact on cotton growth and development (for reviews, see Abdelraheem, O'Connell, Esmaeili, & Zhang, 2019;Dabbert & Gore, 2014); however, at present, only a few studies have been conducted for abiotic stress tolerance in cotton Abdelraheem, Thyssen, et al, 2018;Abdelraheem, Hughs, Jones, & Zhang, 2015;Abdelraheem, Mahdy, & Zhang, 2015;Adams et al, 2011;Levi et al, 2009;Oluoch et al, 2016;Pauli et al, 2016Pauli et al, , 2017Pauli et al, , 2018Saeed et al, 2011;Saranga, Jiang, Wright, Yakir, & Paterson, 2004;Tiwari et al, 2013aTiwari et al, , 2013bZhang et al, 2009). To our knowledge, no QTL study for abiotic stress tolerance has been reported for American pima cotton.…”
Section: Crop Sciencementioning
confidence: 99%
“…Drought tolerance is a complex quantitative trait in plants. QTL mapping and genome-wide association study (GWAS) have been widely used for genetic analysis of drought tolerance related traits in many plants, such as rice [ 4 , 5 ], wheat [ 6 8 ], cotton [ 9 , 10 ] and Brassica napus [ 11 ]. These traits including root length, coleoptile length and shoot length for seedling stage, and yield-related traits for flowering stage.…”
Section: Introductionmentioning
confidence: 99%
“…Drought tolerance is a complex quantitative trait in plants. QTL mapping and genome-wide association study (GWAS) have been widely used for genetic analysis of drought tolerance related traits in many plants, such as rice [4,5], wheat [6][7][8], cotton [9,10] and Brassica napus [11]. These traits including root length, coleoptile length and shoot length for seedling stage, and yield-related traits for owering stage.…”
Section: Introductionmentioning
confidence: 99%